Catalytic Chemical Recycling of Post-Consumer Plastics: A Review - L. M. Affiku; S. O. Okopi; A. S. Akawu; C. N. Abah; K. O. Joseph (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to provide a critical review of Catalytic Chemical Recycling of Post-Consumer Plastics using data from online and in-library resources. The adaptability of plastic has significantly contributed to numerous product innovations and everyday convenience and the waste poses a significant environmental challenge due to its durability and slow degradation rate. Catalytic chemical recycling seen as a promising approach by converting plastic waste into valuable products like fuels and monomers. This process involves breaking down plastic polymers into smaller molecules using catalysts, reducing the need for fossil fuel-based feedstocks. The study explored various catalytic methods, including microwave-assisted, plasma-assisted, supercritical water, and photocatalytic conversion, which can yield high-value products. By promoting catalytic chemical recycling, we can reduce plastic waste, conserve resources, and contribute to a more sustainable future.